Analysis of Errors in the Use of Standard Language in Descriptive Texts for Grade VII Students of SMP Negeri 34 Surabaya - Fitriana Amelia Dewi; Mukhzamilah (Raja Zulkarnain Education Foundation, 2026)
This study aims to identify and describe the types of writing errors made by seventh-grade students at SMP Negeri 34 Surabaya in descriptive texts, including spelling errors, standard word choice, and effective sentences. This study uses S. Pit Corder’s error analysis theory. The data sources for this study come from students’ descriptive texts that contain errors or deviations from the EYD, KBBI, and standard grammar guidelines. The research data is presented in the form of error analysis using a descriptive-qualitative approach in the form of content analysis. The data collection techniques used were observation, interviews, and writing tests. The data analysis techniques used included reduction, data presentation, and conclusion drawing. The results of the study show that from 30 data sources, 505 errors were found, consisting of 444 spelling errors, including 210 errors in the use of capital letters and 26 errors in the use of italics; 46 errors in the use of periods and 62 errors in the use of commas; 17 errors in affixation, 21 errors in prepositions, and 72 errors in word abbreviations. Errors were also found in the selection of standard words (26 errors) and the construction of effective sentences (35 errors). The results of interviews with Indonesian language teachers show that the main cause of writing errors is students’ lack of mastery and understanding of standard writing rules. Based on the results of the study, it can be concluded that students still lack understanding of the use of standard Indonesian grammar, so in-depth learning is needed to improve students’ language skills.